Fatigue and Mental Status of Caregivers of Severely Chronically Ill Patients - Sung-Goo Kang; Sang-Wook Song; Se-Hong Kim; Yi-Jin Kang; Young-Rye Kim; Youngmi Eun (Pain Research and Management)
Background and Aims. Fatigue is an unpleasant experience accompanied by functional deterioration involving both mental and physical factors. Caregivers of patients with severe illnesses who require long-term treatment often experience marked physical and mental fatigue. This study investigated the factors affecting fatigue among caregivers of patients with severe chronic diseases. Methods. The study enrolled 100 caregivers of patients providing home care nursing at a university hospital in Gyeonggi-do of Korea, including 47 caregivers caring for cancer patients and 53 caregivers caring for chronic disease patients (e.g., dementia, amyotrophic lateral sclerosis, and Parkinson’s disease). The degree of fatigue was measured using the Korean version of the multidimensional fatigue inventory (MFI-K). Caregiver depression and anxiety were examined using the Hospital Anxiety and Depression Scale. Results. The average MFI-K score of all caregivers was 60.43 ± 13.77 and did not differ significantly between those caring for cancer patients and those caring for patients with severe chronic diseases (62.15 ± 13.27 vs. 58.49 ± 14.20, respectively, p=0.186). The longer the disease duration, the greater the general and physical fatigue of the caregiver (r = 0.284, p=0.004). However, caregiver mental fatigue did not differ according to disease duration (r = 0.169, p=0.094). The main factors affecting caregiver general and physical fatigue were caregiver anxiety and depression and patient’s disease duration. Conclusions. The caregivers of patients with cancer or chronic severe illnesses experience high levels of fatigue: the longer the disease duration, the greater the degrees of depression, anxiety, and physical fatigue experienced by the caregivers. Such caregivers need strategies to manage their fatigue and depression.